KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL PROBLEM POSING - Aba, Maria Martini; Rukman, Nia Kurniaty; Fatmawati, Agustin (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The Ministry of Education and Culture (2016) states that one of the learning objectives in the 2013 curriculum is to develop creative activities that involve imagination, intuition, and discovery by developing divergent, original thinking, curiosity, making predictions and guesses, and experimenting. The fact that the creative thinking ability of Indonesian students is still low is shown in the results of the Program for International Student Assessment (PISA) in mathematical ability, placing Indonesia at 62 out of 70 countries (OECD, 2016). The provision of problem-posing model questions is expected to stimulate students to think creatively by generating new ideas or ideas to develop existing information and finally students begin to propose new problems according to their understanding of the mathematical concepts being studied. The purpose of this study was to describe students' mathematical creative thinking ability seen from the indicators of creative thinking abilities, namely fluency, flexibility and novelty in solving problem posing question. The research method used is a survey method with the research subject being class VIIIG SMPN 1 Malang. The results obtained, the average score of the fluency indicator is 14.81 or 87.10% in the high category, the average score of the flexibility indicator is 4.64 or 51.61% in the low category, and the novelty indicator is 1.16 or 6, 45% with low category. This shows that the creative thinking ability of students in solving problem-posing questions is low.